Horse Grimace Scale Does Not Detect Pain in Horses with Equine Gastric Ulcer Syndrome. - Ferlini Agne G; May BE; Lovett A; Simon O; Steel C; Santos L; Guedes do Carmo L; Barbosa B; Werner LC; Daros RR; Somogyi AA; Sykes B; et al. (MDPI (Basel, Switzerland), 2023)
Equine gastric ulcer syndrome (EGUS) is a highly prevalent and presumptively painful condition, although the amount of pain horses might experience is currently unknown. The aims of this study were to determine if the Horse Grimace Scale (HGS) could identify pain behaviours in horses with and without EGUS and if severity would be positively associated with the HGS score. Horse grimace scale scores were assessed blindly using facial photographs by seven observers and involved evaluation of 6 facial action units as 0 (not present), 1 (moderately present) and 2 (obviously present). Lameness examination, serum amyloid A (SAA) measurement and gastroscopy evaluation were performed on all horses. Horses (n = 61) were divided into two and three groups based on the presence (yes, no) and severity (none, mild, moderate-severe) of EGUS, respectively. Presence of lameness and elevated SAA (≥50 µg/mL) were used as exclusion criteria. Inter-observer reliability was analyzed by intra-class correlation coefficients (ICC). HGS scores between groups were compared using Welch's and Brown Forsythe tests (p < 0.05). Overall, HGS ICC was "excellent" (0.75). No significant differences (p = 0.566) were observed in HGS scores between horses with and without gastric lesions (mean, 95% CI; 3.36, 2.76-3.95 and 3, 1.79-4.20, respectively). HGS was not influenced by the presence or severity of EGUS in this current study. Further studies investigating the use of different pain scales in horses with EGUS are needed.
Keywords: equine gastric ulcer; glandular gastric disease; grimace; horse grimace scale; horse welfare; pain behaviours; pain scale; squamous gastric disease